Effect of Information and Communication Technology on Career Results: Does Knowledge Sharing Matter? - A., Hameed; Oudah, Ali A. (Medwell Journals, 2014)
This study examines the effects of 2 Information and Communication Technology (ICT) related factors, ICT utilization and perceived ease of ICT usage, on 2 job outcomes, job satisfaction and work effectiveness. On a theoretical basis, the researcher proposed that these effects could be mediated by knowledge sharing. A total of 246 usable responses from full-time employees working in China were analyzed using hierarchical regression analyses which were furthered confirmed by Sobel test and bootstrap-based PROCESS analysis. Results showed that both job satisfaction and work effectiveness were positively related to ICT utilization and perceived ease of IC T usage. Employees knowledge sha ring orientation significantly mediated the relationships of job satisfaction with ICT utilization and ease of ICT usage, as well as the relationships of work effectiveness with these 2 factors. The present study provides further understanding of the mechanism underlying the influences of ICT on employee workplace issues.